A unilateral FLAIR-hyperintense lesions in anti-MOG-associated encephalitis with seizures (FLAMES) case from a developing country: A case report. (December 2022) - Ahmed, Nazeer; Kumari, Jaya; Shahnawaz, Warda; Sami, Hafsa; Naina, Fnu; Hasan, Mohammad; Erum, Sheeza
Abstract: Introduction: The new clinical and radiological entity of the myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is known as the FLAMES syndrome. It will add to the literature and enhance the understanding of this disease. Case presentation: Our case presented a 25-year-old male patient with no known comorbid presented with a generalized sudden headache of moderate intensity for 10 days who came to our hospital. A right-sided upper motor neuron facial palsy was found on the examination. The diagnosis was further confirmed utilizing the MRI scan and the presence of MOG-IgG antibodies. The patient was started on intravenous methylprednisolone which lead to improvement of his symptoms. In the follow-up contrast-enhancing MRI of the brain, the findings suggested near resolution as compared to the initial MRI. Discussion: The FLAMES have been categorized as a subtype of the MOGAD. It is commonly found in males as compared to females and the mean age in which it commonly affects is 29 years with the common age group of 11–46 years. The clinical symptoms and physical signs along with the findings of unilateral cortical FLAMES on MRI suggest the distinctive findings of the FLAMES syndrome. Patients commonly present with symptoms like fever, headache, and cortical symptoms like aphasia. Conclusion: There is a dire need of improving the understanding of this clinic-radiographic syndrome which makes it critically important to ensure the timely diagnosis and prompt consideration of the required medications. Highlights: (MOG) antibody-associated disease (MOGAD) is classified as an inflammatory disease of the central nervous system. Commonly presents with myelitis, optic neuritis, or acute disseminated encephalomyelitis. MRI brain will show fluid-attenuated inversion recovery (FLAIR) hyperintense cortical lesions. Steroids are quite effective in the treatment.